Bioequivalence Evaluation of Two Brands of Lisinopril Tablets by in vitro Comparative Dissolution Test and in vivo Bioequivalence Test - Shin, Meong Cheol; Kim, Jin-Ki; Kim, Chong-Kook (Arzneimittelforschung, 2008)
The bioequivalence of a test formulation (Nanopril®, “test”) and a reference formulation (“reference”) of lisinopril (CAS 83915-83-7) was demonstrated by in vivo and in vitro tests. The in vivo bioequivalence study in 26 healthy volunteers was designed as a single dose, randomized, double-blind trial with a 2-week washout period between the doses. Prior to the in vivo study, an in vitro comparative dissolution test was performed by the paddle method following the bioequivalence guidance of the Korea Food and Drug Administration (KFDA). By the results of the dissolution test it was demonstrated from the similar and rapidly dissolving patterns of the two lisinopril tablets that the two formulations were pharmaceutically equivalent. However, the in vivo bioequivalence study was required to fully evaluate the bioequivalence of the two drug products. In the in vivo bioequivalence study, the plasma samples drawn from the volunteers were analyzed utilizing a sensitive LC-MS-MS analysis method and the bioequivalence between the two drug products was assessed by statistical analysis of the log transformed mean ratios of Cmax, AUC0–tand AUC0–∞. The mean maximum concentration (Cmax) of the test and reference were found to be 60.41 ± 20.07 ng/mL–1 and 61.11 ± 19.36 ng/mL, respectively. The 90% confidence intervals (C.I.) of Cmax were in the range from 0.91 to 1.08. As for the AUC0–t and the AUC0–∞, test values were 792.73 ± 273.41 ng · mL–1 · h, 862.74 ± 303.81 ng · mL–1 · h and the reference values were 841.66 ± 286.07 ng · mL–1 · h, 906.97 ± 318.72 ng · mL–1 · h, respectively. The 90% C. I. of AUC0–twere 0.86 to 1.01 and of AUC0–∞0.87 to 1.02 and thus were within the 80–125% interval proposed by the FDA. In addition to the 90% C. I. of the pharmaceutical parameters, a two-way ANOVA showed no significant difference between the two formulations. Based upon these statistical analyses, it was concluded that the test formulation is bioequivalent to the reference.
Keywords: Angiotensin converting enzyme inhibitors; CAS 83915-83-7; Lisinopril, bioequivalence, dissolution; Nanopril®